Evaluating Urban Public Schools: Parents, Teachers, and State Assessments. (21st February 2013) - Favero, Nathan; Meier, Kenneth J.
<x xml:space="preserve">Abstract</x> Among the most contentious questions in public administration is how the performance of public organizations should be evaluated, and nowhere is this issue more salient than in urban public schools. While significant attention has been devoted to studying administrative measures of public organizations, the views of citizens concerning performance have been widely criticized and are not frequently gathered by schools. How these assessments relate to each other is central to many questions in education policy (e.g., choice, equity) and has important implications for democracy, bureaucratic professionalism, and public performance. This debate can be viewed as focusing on the distinction between convergent validity and discriminant validity. Using data from New York City's public school system with a cross‐sectional time‐series approach, parent and teacher evaluations are compared to government records of schools' characteristics and performance. The findings suggest that parents and teachers are able to conduct intelligent, meaningful evaluations of school quality.